The two forms of capitalism: developmentalism and economic liberalism - LUIZ CARLOS BRESSER-PEREIRA (Brazilian Journal of Political Economy)
ABSTRACT This paper argues that the state and the market are the main institutions regulating capitalism, and, correspondingly, that the form of the economic and political coordination of capitalism will be either developmental or liberal. It defines the developmental state, relates it to the formation of a developmental class coalition, and notes that capitalism was born developmental in its mercantilist phase, turned liberal in the nineteenth century, and, after 1929, became once again developmental, but, now, democratic and progressive. All industrial and capitalist revolutions took place within the framework of developmentalism, whereby the state coordinates the non-competitive sector of the economy and the five macroeconomic prices (which the market is unable to make “right”), while the market coordinates the competitive sector. In the 1970s, a crisis opened the way for a short-lived and reactionary form of capitalism, neoliberalism or rentier-financier capitalism. Since the 2008 Global Financial Crisis, the neoliberal hegemony has come to an end, and we are now experiencing a period of transition.